Injury incidence and patterns in rink hockey: A systematic review - De Pablo, B.; Pena, J.; Moreno, D.; Rodas, G.; Casals, M. (Apunts Sports Medicine, 2022)
This systematic review aims to analyze studies on the extent of injuries in rink hockey athletes. Quality of the reported information was also analyzed. A literature search was performed from January 1992 until August 2020 using the main databases The search terms were: "rink hockey" or the synonym "roller hockey" and "injur*". A total of 11 studies were considered eligible and included. Of these, nine were cross-sectional or descriptive. All samples were non-random, and only one study used a standardized consensus classification of injuries. Muscle strains were the most frequent injuries and lower limbs the most affected body regions. Moreover, overuse was the most common cause, and injury severity was primarily moderate. Injury burden was not reported, and the incidence rate ranged from 3.23-9.7 injuries/1000 h. We conclude that the quality of the reports has room for improvement in terms of study design, outcome, epidemiology measures, and investigation of injury characteristics.